Direct three-dimensional printed egg white hydrogel wound dressing promotes wound healing with hitching adipose stem cells - Wang, Xinhui; Ma, Yuan; Niu, Xingtang; Su, Ting; Huang, Xiaoqi; Lu, Feng; Chang, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
Current wound dressing based on hydrogel offers a promising way to accelerate the healing process, yet great challenges remain in the development of a highly integrated and efficient platform with the combination of therapeutic biomolecules and stem cells. Herein, a natural hydrogel wound dressing from egg white can be conveniently obtained by feasible physical crosslinking, the prepared hydrogel dressing features interconnected microporous channels, direct 3D printing, cytocompatibility, and intrinsic biomolecules to advance cell behavior. The 3D printed egg white hydrogels promote the adhesion and proliferation of adipose-derived stem cells (ASCs) without obvious cytotoxicity. In addition, this integrated hydrogel platform accompanied with ASCs accelerates wound healing through the enhancement of fibroblast proliferation, angiogenesis, and collagen rearrangement in the wound bed. The egg white hydrogel provides an effective wound caring product possessing low cost, easy availability along with ready manufacturing, and advanced therapeutic effect, which may be extended for the management of chronic or other complicated wounds.